Temporal monitoring of the nor-1 (aflD) gene of Aspergillus flavus in relation to aflatoxin B-1 production during storage of peanuts under different water activity levels - Abdel-Hadi, Ahmed; Carter, D; Magan, Naresh (Blackwell Publishing Ltd, 2010)
Aims: A relative quantification system (RQ-PCR) was used to monitor the correlations between the activity of the nor-1 (=aflD) gene of Aspergillus flavus using real-time PCR in relation to phenotypic aflatoxin B-1 (AFB(1)) production and populations of A. flavus in stored peanuts at three water activity levels (a(w), 0.95, 0.90 and 0.85) for 6 weeks. Methods and Results: Real-time PCR was used to amplify the nor-1 gene (target gene), and benA56 (beta-tubulin gene) used as a control gene. Expression of three structural genes, nor-1 (=aflD), ver-1 (=aflM), and omtA (=aflP), and the regulatory gene aflR of the aflatoxin biosynthetic pathway were also assayed. There were significant differences between nor-1 gene expression at the three a(w) levels; higher expression at 0.90 a(w) in weeks 1-3, when compared to 0.95. In contrast, in the driest treatment (0.85 a(w)) none or very low nor-1 expression occurred. The populations of A. flavus colony-forming units (CFUs g(-1)) increased over time with the highest at 0.95 a(w). Highest AFB(1) production was at 0.90 and 0.95 a(w) from weeks 3-6. A(w) had a significant effect on aflR transcription at 0.95 a(w) over the 6-week period, while at 0.90 a(w), only in the last 2 weeks. Conclusions: Correlations between different factors showed that log AFB(1) x log CFUs, log AFB(1) x a(w), and log CFUs x a(w) were statistically significant, while log CFUs x RQ-PCR and RQ-PCR x a(w) were not. The AflR gene may not have an important role in the regulation of nor-1 expression in food matrices (e. g. peanuts). Significance and Impact of the study: Determination of correlations between nor-1 expression and aflatoxin production by A. flavus in raw peanuts under different a(w) levels could be helpful to predict potential risk of aflatoxin production during storage of this hygroscopic food product and minimize contamination with the AFB(1).
Keywords: aflatoxin genes aflatoxins Aspergillus flavus CFUs peanuts real-time PCR polymerase-chain-reaction real-time pcr section flavi united-states rt-pcr biosynthesis growth quantification parasiticus mycotoxins